Chemically Polymerization Mechanism of Aromatic Compounds under Atmospheric Pressure Plasma Conditions. Issue 5 (2nd May 2013) - Asandulesa, Mihai; Topala, Ionut; Pohoata, Valentin; Legrand, Yves Marie; Dobromir, Marius; Totolin, Marian; Dumitrascu, Nicoleta
Abstract: The multitude of chemically reactive species that are involved in plasma polymerization process make difficult to anticipate how the polymer will look like. In order to prepare polymerized films with imposed properties a good control over the plasma polymerization reaction should be done. In this paper, we investigate plasma polymerization reactions of aromatic compounds using a cold atmospheric pressure glow discharge working in helium. The structure of polymerized films was determined using infrared spectroscopy, X‐ray photoelectron spectroscopy, and nuclear magnetic resonance spectroscopy. Furthermore, the results of spectroscopic analyses allowed us to develop a polymerization mechanism from a chemical point of view related to formation of plasma‐polymerized films. Abstract : In this paper, we describe the successful synthesis of polymer films in atmospheric pressure plasma conditions, from different aromatic compounds. The polymeric films were investigated by means of FT‐IR, XPS, and 1 H NMR techniques. A polymerization mechanism of aromatic compounds is developed from the chemical composition of films and is based on plasma‐induced radical chain‐growth concept.